The Alkali-Tolerant Bacterium of Bacillus thuringiensis EM-A1 Can Effectively Perform Heterotrophic Nitrification and Aerobic Denitrification - Wang, Tingjiang; Chen, Mengping; Liang, Xiwen; Chen, Fali; He, Tengxia; Li, Zhu (Frontiers in Environmental Science, 2022)
Removal of nitrogen from hydroxylamine could effectively improve the wastewater treatment efficiency. In this work, Bacillus thuringiensis EM-A1 was obtained from a biogas digester with hydroxylamine as the only nitrogen source. Hydroxylamine (100%) and total nitrogen (71.86%) were efficiently removed under the following conditions: 30°C, sucrose as carbon source, carbon to nitrogen ratio 40, rotation speed 150 rpm, pH 9.58, and inoculant concentration of 0.58×108 colony-forming units. Ammonium was completely consumed by strain EM-A1, and 8.32 ± 0.08 mg/L of nitrate was produced during the ammonium removal process. During aerobic denitrification, the removal efficiencies of NO2−-N and NO3−-N by strain EM-A1 were 100 and 76.67%, respectively. There were about 29.34 ± 0.18%, 26.71 ± 0.36%, and 23.72 ± 0.88% initial total nitrogen lost as nitrogenous gas when NH4+, NO3−, and NO2− were separately used as the sole nitrogen source. The specific activities of ammonia monooxygenase, hydroxylamine oxidoreductase, nitrate reductase, and nitrite oxidoreductase were successfully detected as 0.37, 0.88, 0.45, and 0.70 U/mg protein, respectively. These results indicated that B. thuringiensis EM-A1 is a promising candidate for bioremediation of inorganic nitrogen from wastewater.